Fire Retardancy and Thermal Degradation Kinetics of Epoxy Composites Containing Polyaminopropylphenylsilsesquioxane. Issue 5 (7th April 2021) - Bao, Xiaohui; Wu, Fangyi; Wang, Jiangbo
Abstract: Polyaminopropylphenylsilsesquioxane (PA) was proved to be an effective fire retardant for epoxy resin (EP) by cone calorimeter measurements, since a significant peak heat release rate (PHRR) reduction of 42% was achieved from the EP/PA fire retardant epoxy (FREP) system relative to the pure EP. The thermal degradation behavior was investigated by thermogravimetric analysis (TGA) and the fire-retardant mechanism of the FREP system was studied by kinetics analysis methods, including the Kissinger method and the Flynn-Wall-Ozawa method. The calculated results of the Kissinger method showed that the activation energy of the FREP was slightly lower than that of pure EP. The Flynn-Wall-Ozawa method further revealed that the addition of the fire retardant PA increased the activation energies of FREP thermal degradation in the final stage, which illustrated that PA promoted the thermal degradation of EP in the early and middle stages and subsequently, stabilized the char residues and improved the fire retardancy of FREP in the thermal degradation process.